2020
DOI: 10.3389/fimmu.2020.01276
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Cross-Presentation by Macrophages

Abstract: The contribution of dendritic cell (DC) antigen cross-presentation to the activation of CD8 + T lymphocytes for immune defense against tumors, viruses, and intracellular pathogens has been recognized widely. Although originally thought to be an exclusive characteristic of DCs, recently also other immune cells, particularly macrophages, have been shown capable of cross-presentation. Here we provide an overview of in vitro and in vivo evidence on cross-presentation by macrophages. As we discuss, it is now firmly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
99
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(101 citation statements)
references
References 77 publications
(169 reference statements)
2
99
0
Order By: Relevance
“…This process is necessary to recognize and destroy tumor cells as well as viruses that do not readily infect antigen-presenting cells, stimulating naïve T cells into activated CTLs [ 14 , 20 , 21 ]. Specifically, cross-presentation involves dendritic cells (DCs) which present TAAs/TSAs or pathogen-derived peptides in their HLA class I complex to naïve T cells [ 22 , 23 , 24 ]. Extracellular peptide loading on HLA class I complex differs from the canonical way followed by intracellular peptides and it will be discussed below in this review.…”
Section: Human Leucocyte Antigen and Antigen Presentation Machinermentioning
confidence: 99%
See 1 more Smart Citation
“…This process is necessary to recognize and destroy tumor cells as well as viruses that do not readily infect antigen-presenting cells, stimulating naïve T cells into activated CTLs [ 14 , 20 , 21 ]. Specifically, cross-presentation involves dendritic cells (DCs) which present TAAs/TSAs or pathogen-derived peptides in their HLA class I complex to naïve T cells [ 22 , 23 , 24 ]. Extracellular peptide loading on HLA class I complex differs from the canonical way followed by intracellular peptides and it will be discussed below in this review.…”
Section: Human Leucocyte Antigen and Antigen Presentation Machinermentioning
confidence: 99%
“…Extracellular peptide loading on HLA class I complex differs from the canonical way followed by intracellular peptides and it will be discussed below in this review. However, recently, several lines of evidence demonstrated that macrophages are also able to implement a cross-presentation process, subverting the original belief that it is an exclusive characteristic of DCs [ 22 ].…”
Section: Human Leucocyte Antigen and Antigen Presentation Machinermentioning
confidence: 99%
“…The underlying mechanism for this phenomenon is unknown, but it is consistent with the cell biology of antigen presentation in response to TLR stimulation. TLR signaling can induce phagosomal MHC-I delivery to enhance TAP recruitment to endosomes [ 26 , 27 ], which is beneficial for antigen cross-presentation [ 28 ]. The peptide-mediated undocking of MHC class I is linked to the transport cycle of TAP1 [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The host’s DNA sensing of VV is complex and hence an attenuated VV strain, such as MVA or genetically engineered mice is widely used to gain insights into VV immunity. However, a limitation is that DNA sensing in mice differs from humans [ 230 , 231 ]. Several studies indicated that type I IFN production by MVA is dependent of cGAS and its downstream adaptor STING [ 227 , 232 ].…”
Section: Cyclic Gmp-amp Synthasementioning
confidence: 99%
“…NK cells are also involved in adaptive immune response, since they cross talk with DC in several ways, including killing of immature DCs and promoting DC maturation, which leads to overall enhanced antigen presentation to T cell [ 246 ]. Similarly, macrophages also function as antigen presenting cells, thus contributing to the activation of T helper cell [ 230 ].…”
Section: Prr In Activation Of Adaptive Immune Responsementioning
confidence: 99%